If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3x + -2 = 9 + -8x Reorder the terms: -2 + 3x = 9 + -8x Solving -2 + 3x = 9 + -8x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '8x' to each side of the equation. -2 + 3x + 8x = 9 + -8x + 8x Combine like terms: 3x + 8x = 11x -2 + 11x = 9 + -8x + 8x Combine like terms: -8x + 8x = 0 -2 + 11x = 9 + 0 -2 + 11x = 9 Add '2' to each side of the equation. -2 + 2 + 11x = 9 + 2 Combine like terms: -2 + 2 = 0 0 + 11x = 9 + 2 11x = 9 + 2 Combine like terms: 9 + 2 = 11 11x = 11 Divide each side by '11'. x = 1 Simplifying x = 1
| 576(72)=d | | x^4-7x^2+20=0 | | 5x+8=6x | | 2x+y-2z=-3 | | 1.6/24=n/60 | | 3y/8-2=4 | | 2v^2+7v+5= | | 4-5n=2-3n | | -4x+4-30-18x=.33 | | w^2+4w= | | 8k-=23-k-3k | | 5x-4=3n+2 | | K-5/6=-7 | | 2t=-13 | | 16s^2+24s+9= | | 3(2)+6(8+2)= | | B+10.8=12.80 | | 10=s/2+78 | | 1/3x=6-1/5x | | 3x+2(x+1)=6x+(3x-4) | | 7n-20=-48 | | c^2+14c+45= | | m^2+6m+4=-4 | | 4i(6+2i)= | | y=3.0x+1.7 | | 6x+3=12-2x | | t(5t+2)= | | 276/12 | | Y=6x^2+x-15 | | -(-21y+29)-21y=-(19y+23)+26 | | 4m+6m+7m= | | 81w^2-49= |